Youth's Overseas Employment and Entrepreneurship: The Case of Taiwan. Issue 6 (3rd May 2022) - Lin, Ya-Chi; Lin, Chan-Hui; Chen, Shin-Hui; Yeh, Kuo-Chun
ABSTRACT: Taiwan's brain drain has been a significant concern due to China's strong economic drawing power, and the situation may have worsened over the past decade. In the literature, the causes and influence of human capital outflow are uncertain, but the outflow of younger workers can be a problem for the future domestic economic growth. This paper explores the determinants for Taiwan's youth overseas employment and entrepreneurship using the questionnaire administered in 2015 for residents between 20–45 years old. A binary logit model and robustness tests investigate the push and pull factors directing Taiwan's youth to go abroad. Corresponding to changes in Taiwan's economic diplomatic policy, we focus on China (including the mainland, Hong Kong, and Macao) and Southeast Asia (including Australia, India, and other Oceanic economies) as the two main destination areas. The data do not show clear evidence to support Taiwan's brain drain by 2016, especially in the case of employees with a master's education or above in high tech and financial sectors. In contrast, personal considerations, such as broadening international vision and resolving career bottlenecks are more important influences for Taiwan's youth to seek employment in China.